Advances in the use of exosomes for the treatment of ALI/ARDS - Liu, Chang; Xiao, Kun; Xie, Lixin (Frontiers in Immunology, 2022)
Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a critical clinical syndrome with high morbidity and mortality. Currently, the primary treatment for ALI/ARDS is mainly symptomatic therapy such as mechanical ventilation and fluid management. Due to the lack of effective treatment strategies, most ALI/ARDS patients face poor prognosis. The discovery of exosomes has created a promising prospect for the treatment of ALI/ARDS. Exosomes can exert anti-inflammatory effects, inhibit apoptosis, and promote cell regeneration. The microRNA contained in exosomes can participate in intercellular communication and play an immunomodulatory role in ALI/ARDS disease models. This review discusses the possible mechanisms of exosomes in ALI/ARDS to facilitate the development of innovative treatments for ALI/ARDS.